Rapid screening for Neurospora crassa strains lacking CuZn superoxide dismutase (sod-1) - Donald O. Natvig; Trang Nguyen (Fungal Genetics Reports, 1993)
We have developed a simple system for determining if strains of N. crassa produce functional CuZn superoxide dismutase. We previously isolated N. crassa mutants with null alleles of the sod-1 gene, which encodes this enzyme (Chary et al. submitted).